The Influence of Macroeconomic Variables on Foreign Direct Investment in the Manufacturing Industry Sector in Indonesia - Nidya Ayu Setya Ningrum; Inayati Nuraini Dwiputri (Jurnal Ekonomi Pembangunan, 2024)
The purpose of this research is to examine the effect of macroeconomic variables in the form of economic growth, inflation, exchange rates, interest rates, and the money supply on Foreign Direct Investment in the manufacturing industry sector in Indonesia and see whether the presence of the Covid -19 pandemic has affected FDI in the manufacturing sector in Indonesia. Indonesia in the short and long terms. This research was conducted for 13 years every quarter, starting in 2010-2022, because, since 2010 until now, the manufacturing sector has made the most significant contribution to Indonesia's GDP. This study was analyzed using Autoregressive Distributed Lag (ARDL) with a dummy variable. The research results show that short-term economic growth increases FDI in Indonesia's manufacturing sector. The variables of inflation, interest rates, total money in circulation, and the COVID-19 pandemic have implications for reducing FDI flows in the manufacturing sector in Indonesia. Meanwhile, the exchange rate does not significantly affect FDI in Indonesia's manufacturing sector. In the long term, economic growth and inflation variables increase the flow of FDI in the manufacturing sector. Interest rates have had the effect of reducing FDI flows in Indonesia's processing industry sector. Meanwhile, the exchange rate, total money in circulation, and the COVID-19 pandemic have no long-term impact on FDI in Indonesia's manufacturing industry sector in the long term.